Comparison of Lesional Juvenile Myositis and Lupus Skin Reveals Overlapping Yet Unique Disease Pathophysiology. Issue 6 (2nd May 2021) - Turnier, Jessica L.; Pachman, Lauren M.; Lowe, Lori; Tsoi, Lam C.; Elhaj, Sultan; Menon, Rajasree; Amoruso, Maria C.; Morgan, Gabrielle A.; Gudjonsson, Johann E.; Berthier, Celine C.; Kahlenberg, J. Michelle
Abstract : Objective: Skin inflammation heralds systemic disease in juvenile myositis, yet we lack an understanding of pathogenic mechanisms driving skin inflammation in this disease. We undertook this study to define cutaneous gene expression signatures in juvenile myositis and identify key genes and pathways that differentiate skin disease in juvenile myositis from childhood‐onset systemic lupus erythematosus (SLE). Methods: We used formalin‐fixed paraffin‐embedded skin biopsy samples from 15 patients with juvenile myositis (9 lesional, 6 nonlesional), 5 patients with childhood‐onset SLE, and 8 controls to perform transcriptomic analysis and identify significantly differentially expressed genes (DEGs; q ≤ 5%) between patient groups. We used Ingenuity Pathway Analysis (IPA) to highlight enriched biologic pathways and validated DEGs by immunohistochemistry and quantitative real‐time polymerase chain reaction. Results: Comparison of lesional juvenile myositis to control samples revealed 221 DEGs, with the majority of up‐regulated genes representing interferon (IFN)–stimulated genes. CXCL10, CXCL9, and IFI44L represented the top 3 DEGs (fold change 23.2, 13.3, and 13.0, respectively; q < 0.0001). IPA revealed IFN signaling as the top canonical pathway. When compared to childhood‐onset SLE, lesional juvenile myositis skin shared a similar gene expression pattern, with only 28 unique DEGs, including FBLN2, CHKA, and SLURP1 . Notably, patients with juvenile myositis who were positive for nuclear matrix protein 2 (NXP‐2) autoantibodies exhibited the strongest IFN signature and also demonstrated the most extensive Mx‐1 immunostaining, both in keratinocytes and perivascular regions. Conclusion: Lesional juvenile myositis skin demonstrates a striking IFN signature similar to that previously reported in juvenile myositis muscle and peripheral blood. Further investigation into the association of a higher IFN score with NXP‐2 autoantibodies may provide insight into disease endotypes and pathogenesis.